Depression and Anxiety in patients undergoing Hemodialysis - Sar Sikandar Ali Khan, Abid Aftab, Muhammad Sheraz Afzal Malik, Syed Shah Khalid, Munsif Ali, Ata Ullah (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients undergoing hemodialysis for End Stage Kidney Disease (ESKD) face numerous physical and emotional challenges, making them vulnerable to psychological disorders such as anxiety and depression. These mental health conditions can negatively impact treatment adherence, quality of life, and overall prognosis. Objectives: The present study aimed to assess the prevalence of anxiety and depression among patients undergoing hemodialysis at the Combined Military Hospital (CMH), Lahore, and to identify the levels of severity associated with these conditions. Methodology: A cross-sectional research design was employed using purposive non-probability sampling. The sample consisted of 50 literate hemodialysis patients who had undergone at least three dialysis sessions and did not have any other severe illnesses. Data collection tools included a demographic information sheet, the Hamilton Anxiety Rating Scale (HAM-A), and the Hamilton Depression Rating Scale (HAM-D). Ethical approval was obtained, and data were analyzed using descriptive statistics via SPSS. Results: Findings revealed that 24% of participants experienced moderate to severe levels of depression, while 24% exhibited moderate to severe anxiety. The majority of participants were middle-aged, male, and belonged to middle-income households. Coexisting conditions such as hypertension were prevalent in 72% of patients. The psychological distress observed suggests a strong association between chronic illness and emotional well-being. Conclusion: The study emphasizes the need for routine psychological screening and mental health support in dialysis settings to improve patient outcomes and enhance quality of life. Keywords: Hemodialysis, End Stage Kidney Disease, Anxiety, Depression, Mental Health, Psychological Assessment, Chronic Illness.